Basic principles of cardiothoracic surgery training: a position paper by the European Association for Cardiothoracic Surgery Residents Committee. (26th August 2022) - Zientara, Alicja; Hussein, Nabil; Bond, Chris; Jacob, Kirolos A; Naruka, Vinci; Doerr, Fabian; Nägele, Felix; Pölzl, Leo; Eid, Maroua; Jarral, Omar; Cerqueira, Rui; Haunschild, Josephina; et al.
Abstract: OBJECTIVES: Across Europe there are significant variations in the fundamental structure and content of cardiothoracic surgery (CTS) training programmes. Previous efforts have been made to introduce a Unified European Training System, which outlined the fundamentals of the ideal programme and supported a paradigm shift from an apprenticeship to a competency-based model. This article's goal was to define key structural, administrative and executive details of such a programme to lay the foundations for the standardization of cardiothoracic surgical training across Europe. METHODS: The European Association for Cardiothoracic Surgery Residents Committee had previously conducted a residents' training survey across Europe in 2020. Training curricula from the twelve most represented countries across Europe were either searched online or obtained from the countries' national trainee representative and reviewed by the committee. Information was collated and placed into one of the following categories to develop the position paper: (i) selection of eligible candidates, (ii) guidance for an outcome-based syllabus, (iii) documentation and evaluation of training progress, (iv) mandatory rotations and training courses, (v) number of independent or assisted cases and (vi) requirements and quality assurance of teachers. RESULTS: An independent professional body should promote an outcome-based syllabus and take responsibility for the training programme's quality assurance. Trainees should be selected on merit by an open and transparent process. Training should be delivered within a defined period and supervised by an appointed training committee to ensure its implementation. This committee should review the trainees progression regularly, provide feedback and offer trainees the opportunity to experience various training environments and trainers. A common electronic portal be used by trainees to record their agreed objectives and to evidence their completion. Trainees should regularly attend specialty-relevant courses and conferences to promote professional and academic development. The end of training is reached when the formal requirements of the training programme are met and the trainee is able to perform at the level expected of a day-1 independent surgeon. CONCLUSIONS: This article defines the key structural, administrative, and executive principles for CTS training. Programmes are encouraged to review and modify their training curricula, if necessary, to ensure the delivery of high-quality, standardized, outcome-orientated CTS training across Europe. Abstract : Cardiothoracic computed tomography (CT) and cardiovascular surgery is an ever developing and innovative surgical specialization.